International Pediatric ORL Group (IPOG) Robin Sequence consensus recommendations. (March 2020) - Fayoux, Pierre; Daniel, Sam J.; Allen, Gregory; Balakrishnan, Karthik; Boudewyns, An; Cheng, Alan; De Alarcon, Alessandro; Goel, Dimple; Hart, Catherine K.; Leboulanger, Nicolas; Lee, Gi; Moreddu, Eric; et al.
Abstract: Objective: To provide recommendations for the comprehensive management of airway obstruction in patients with Robin Sequence. Methods: Expert opinion by the members of the International Pediatric Otolaryngology Group (IPOG). Results: The consensus statement provides recommendations for medical specialists who manage infants with Robin Sequence including: evaluation and treatment considerations for commonly debated issues in post-natal airway obstruction, assessment of antenatal obstruction and perinatal airway management. Conclusion: Consensus recommendations are aimed at improving management of airway obstruction in patients with Robin Sequence.